How Much Oil is the Islamic State Group Producing? Evidence from Remote Sensing - Do, Quy-Toan (World Bank E-Library Archive, 2017)
Accurately measuring oil production in low-governance contexts is an important task. Many terrorist organizations and insurgencies-including the Islamic State group, also known as ISIL/ISIS or Daesh-tap oil as a revenue source. Understanding spatial and temporal variation in production in their territory can help address such threats by providing near real-time monitoring of their revenue streams, helping to assess long-term economic potential, and informing reconstruction strategies. More broadly, remotely measuring extractive industry activity in conflict-affected areas and other regions without reliable administrative data can support a broad range of public policy decisions and academic research. This paper uses satellite multi-spectral imaging and ground-truth pre-war output data to effectively construct a real-time day-to-day census of oil production in areas controlled by the terrorist group. The estimates of production levels were approximately 56,000 barrels per day (bpd) from July-December 2014, drop to an average of 35,000 bpd throughout 2015, before dropping further to approximately 16,000 bpd in 2016